Urbach’s rule peculiarities in structures with CdSxSe₁₋x nanocrystals - Kunets, V.P.; Kulish, N.R.; Kunets, Vas.P.; Lisitsa, M.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
We have found that the long wavelength fundamental absorption edge of CdSXSe₁-x nanocrystals grown in an oxide glass follows to the generalized Urbach rule that takes into account both the dynamic (phonon induced) and static (defect induced) disorders of nanocrystal lattice. Temperature intervals with the dominant influence of both disorders on the absorption edge were determined. We have also estimated Urbach rule constants comparing them with the bulk ones. Using various Urbach`s rule theories we analyzed the most considerable changes of nanocrystal parameters when their sizes are decreased down to the quantum scale. It was found that the exciton-phonon coupling constant and exciton localization one are increased; the average electric fields induced by phonons and charged point defects are also increased.